The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0204928
|View full text |Cite
|
Sign up to set email alerts
|

Limited field radiation therapy results in decreased bone fracture toughness in a murine model

Abstract: Fragility fractures are a well-known complication following oncologic radiotherapy, and it is suspected that radiation-induced embrittlement of bone within the treatment field may contribute to fracture risk. To explore this phenomenon, a mouse model (BALB/cJ) of fractionated, limited field, bilateral hindlimb irradiation (4x5 Gy) was used. The effects of radiation on femoral (cortical) bone fracture toughness, morphology, and biochemistry—including advanced glycation end products (AGEs)—were quantified and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 77 publications
(79 reference statements)
3
40
2
1
Order By: Relevance
“…There was no apparent collagen fragmentation in tibiae from the nonirradiated control group or the groups receiving therapeutic doses of radiation (0 and 12 weeks post-RTx, and 20 Gy ex vivo; Figure 6). F I G U R E 7 Instability fracture toughness of mineralized cortical bone (as we previously reported) 11 increased with greater demineralized bone energy to failure. Mean and SE of mean shown with all-time points grouped together results in loss of bone strength, 24,25,35 diminished fracture toughness, 35,36 and fragmentation of bone collagen.…”
Section: Collagen Fragmentationmentioning
confidence: 66%
See 4 more Smart Citations
“…There was no apparent collagen fragmentation in tibiae from the nonirradiated control group or the groups receiving therapeutic doses of radiation (0 and 12 weeks post-RTx, and 20 Gy ex vivo; Figure 6). F I G U R E 7 Instability fracture toughness of mineralized cortical bone (as we previously reported) 11 increased with greater demineralized bone energy to failure. Mean and SE of mean shown with all-time points grouped together results in loss of bone strength, 24,25,35 diminished fracture toughness, 35,36 and fragmentation of bone collagen.…”
Section: Collagen Fragmentationmentioning
confidence: 66%
“…Using a mouse model of unilateral hindlimb limited field radiotherapy, we have previously demonstrated that therapeutic radiation results in loss of femoral metaphyseal trabecular structures (decreased trabecular bone volume fraction, decreased trabecular number, decreased connectivity density, and increased trabecular spacing) subsequent to increased osteoclastic activity, diminished bone strength (axial compression testing of distal femur, femoral diaphyseal bending strength), and decreased femoral diaphyseal fracture toughness without loss of bone density. [11][12][13][14] Work in other labs has supported these findings. [15][16][17] Furthermore, we have shown that the bone matrix (organic and collagen phases) becomes increasingly aligned post-RTx, accompanied by an increase in trivalent:divalent collagen crosslink ratio as measured by Raman spectroscopy, with only small transient changes in pathologic crosslinks and adducts such as advanced glycation end products (AGEs).…”
mentioning
confidence: 57%
See 3 more Smart Citations